Accumulation of cytotoxic T cells in the aged CNS leads to axon degeneration and contributes to cognitive and motor decline - Groh, Janos; Knoepper, Konrad; Arampatzi, Panagiota; Yuan, Xidi; Loesslein, Lena; Saliba, Antoine-Emmanuel; Kastenmuller, Wolfgang; Martini, Rudolf (Nature Aging, 2021)
Aging is a major risk factor for the development of nervous system functional decline, even in the absence of diseases or trauma. The axon–myelin units and synaptic terminals are some of the neural structures most vulnerable to aging-related deterioration1–6, but the underlying mechanisms are poorly understood. In the peripheral nervous system, macrophages—important representatives of the innate immune system—are prominent drivers of structural and functional decline of myelinated fibers and motor endplates during aging7. Similarly, in the aging central nervous system (CNS), microglial cells promote damage of myelinated axons and synapses8–20. Here we examine the role of cytotoxic CD8+ T lymphocytes, a type of adaptive immune cells previously identified as amplifiers of axonal perturbation in various models of genetically mediated CNS diseases21 but understudied in the aging CNS22–25. We show that accumulation of CD8+ T cells drives axon degeneration in the normal aging mouse CNS and contributes to age-related cognitive and motor decline. We characterize CD8+ T-cell population heterogeneity in the adult and aged mouse brain by single-cell transcriptomics and identify aging-related changes. Mechanistically, we provide evidence that CD8+ T cells drive axon degeneration in a T-cell receptor- and granzyme B-dependent manner. Cytotoxic neural damage is further aggravated by systemic inflammation in aged but not adult mice. We also find increased densities of T cells in white matter autopsy material from older humans. Our results suggest that targeting CD8+ CNS-associated T cells in older adults might mitigate aging-related decline of brain structure and function.
CRIS-Team Scopus Importer:2023-03-23